16 Cangrelor versus ticagrelor in primary percutaneous coronary intervention: platelets, microcirculation and infarct size. (25th January 2018) - Ubaid, Salahaddin; Ford, Tom; Berry, Colin; Khogali, Saib; Wrigley, Ben; Munir, Shahzad; Martins, Joe; Townend, Jon; McAlindon, Elisa; Cotton, James
Abstract : Background: Oral P2Y12 inhibitors have a delayed onset of action in ST-segment elevation myocardial infarction (STEMI) patients. We describe the first randomised controlled trial comparing Cangrelor with Ticagrelor in the context of primary percutaneous coronary intervention (PPCI). Methods: 100 subjects with first acute STEMI were randomised on arrival to Ticagrelor (180 mg then 90 mg bd) or Cangrelor (bolus then infusion). Cangrelor treated subjects received Ticagrelor 30 min prior to infusion end. All patients received Aspirin 300 mg. Platelet P2Y12 inhibition was assessed using VerifyNow at first coronary balloon inflation, 4 and 24 hours post drug initiation. Coronary microcirculation was assessed after PPCI by calculating the index of microvascular resistance (IMR). ST-segment resolution at 90 min was measured and the corrected TIMI frame count, flow grade and myocardial perfusion grade were calculated. Peak Troponin level at 24 hours and infarct size at 12 weeks were measured by cardiac magnetic resonance imaging (CMRI) (ClinicalTrials.gov NCT02733341 ). Results: P2Y12 inhibition was markedly greater in the Cangrelor group (PRU 145.2 vs 248.3 p<0.0001) at balloon inflation. At 4 hours (158.1 vs 131.2 p=ns) and 24 hours (61.0 vs 60.1 p=ns) readings were similar. Despite this early more potent antiplatelet effect, no difference was seen in terms of IMR, ST-segment resolution, and angiographic measures of improved reperfusion or final infarct size. Conclusion: Early, more potent P2Y12 inhibition with Cangrelor does not translate into improved measures of microcirculatory function or infarct size.